Pathoanatomy of the Anterolateral Tibial Fragment in Ankle Fractures - Rammelt, Stefan; Bartoníček, Jan; Kroker, Livia (The Journal of bone and joint surgery. American volume, 2022)
BACKGROUND: The anterior distal tibial tubercle provides attachment to the anterior tibiofibular syndesmosis. It may be considered a fourth, or anterior, malleolus (AM). Fractures of the AM may extend into the tibial incisura and tibial plafond. The purpose of this study was to analyze the pathoanatomy of AM fractures and associated ankle injuries. METHODS: One hundred and forty patients (median age, 61.0 years) with a total of 140 acute malleolar fractures (OTA/AO 44) involving the anterolateral distal tibial rim were analyzed with computed tomography (CT) imaging. All components of the malleolar fractures were analyzed and classified. Fracture patterns were compared with those of all patients with malleolar fractures treated during the same 9-year period. Patients with fractures of the tibial pilon (OTA/AO 43) and patients <18 years of age were excluded. RESULTS: Of the 140 AM fractures, 52.9% were classified as type 1 (extra-articular avulsion); 35.7%, type 2 (incisura and plafond involvement); and 11.4%, type 3 (impaction of the anterolateral plafond). The fibula was fractured in 87.1%; the medial malleolus, in 66.4%; and the posterior malleolus, in 68.6%. An isolated AM fracture was seen in 4.3%. The size of the AM fractures correlated negatively with that of the posterior malleolar fractures. The proportion of pronation-abduction fractures increased and the proportion of supination-external rotation fractures decreased as the type of AM fracture increased. A fracture involving the AM occurred in 12.6% of all ankle fractures and occurred significantly more frequently in pronation-type injuries and elderly patients. No supination-adduction fractures with AM involvement were seen. The intraclass correlation coefficient for the proposed classification of the AM fractures was 0.961 (95% confidence interval [CI] = 0.933 to 0.980) for interobserver agreement and 0.941 (95% CI = 0.867 to 0.974) for intraobserver agreement. CONCLUSIONS: Knowledge of the 3D pathoanatomy of AM fractures and associated malleolar fractures may help with surgical decision-making and planning. CT imaging should be employed generously in the diagnosis of complex ankle fractures, in particular with pronation-type injuries. CLINICAL RELEVANCE: Depending on the individual 3D fracture pattern, fixation of displaced anterolateral distal tibial fragments potentially contributes to the restoration of joint congruity, tibiofibular alignment, and syndesmotic stability in complex malleolar fractures.
Keywords: Female; Preoperative Care; lidé středního věku; hlezenní kloub; Tomography, X-Ray Computed; mužské pohlaví; senioři nad 80 let; Ankle Joint; Humans; tibie; dospělí; Tibia; předoperační péče; fraktury kotníku; lidé; Middle Aged; počítačová rentgenová tomografie; Aged, 80 and over; senioři; vnitřní fixace fraktury; ženské pohlaví; Ankle Fractures; Aged; Fracture Fixation, Internal; Adult; Male